GEOPOLITICS OF INTERDEPENDENCE BETWEEN KAZAKHSTAN AND OTHER CIS COUNTRIES (Conceptual Aspect of Interaction) - RINGROSE, Gulnar (CENTRAL ASIA AND THE CAUCASUS, 2005)
The currents geopolitical situation that determines the key aspects of Kazakhstan’s socioeconomic development has a distinctly regional character. In the context of global development trends, the economic and political importance of Central Asia depends on two groups of factors: its geographical proximity to such great powers as Russia and China, and its abundant natural resources, especially oil, gas and nonferrous metals. These groups of factors, for their part, are made up of numerous constituents, which are closely intertwined and are in a state of dynamic imbalance. The geostrategic interest taken by leading countries of the world in the economy of the Republic of Kazakhstan is due precisely to its resource potential and specific geopolitical position. The mineral resource base of Kazakhstan, just as of all other FSU republics, was formed with due regard for the needs of the U.S.S.R. as a closed economic space, while the deployment of consumers of mineral resources was dictated by the principles of large-scale integration, which was often conducive to highly efficient use of the all-Union mineral potential. For example, major titanium and zirconium deposits in Ukraine provided all the necessary raw materials for three titanium-magnesium integrated works located in different parts of the U.S.S.R.: Zaporozhye (Ukraine), Berezniki (R.S.F.S.R.) and Ust-Kamenogorsk (Kazakhstan), and also resolved all the problems in providing Soviet plants with zircon. The unique deposits of magnetic iron ore in Northern Kazakhstan supplied raw materials for steel mills in the Urals and Western Siberia, and the creation of the U.S.S.R.’s largest mineral resource base for the production of bauxites, also in Northern Kazakhstan, ensured the steady operation of the country’s aluminum subindustry. 1 Today Kazakhstan’s major geopolitical partners—Russia, U.S.A., PRC and Britain—are attracted by its abundant mineral and agricultural resources, and also by its advantageous geostrategic position in Central Asia at the junction of transportation routes running to Russia and China. In addition, this factor helps Kazakhstan to take a regional lead in developing economic transformation processes. 2 The geo-economic and geopolitical advantages of our state—its location in the center of Eurasia at the intersection of the shortest transcontinental transportation and communication routes—are of interest to large foreign companies and transnational corporations, giving the republic a chance to turn transit through its territory into a key revenue item of the state budget. This advantage also enables the country to attract foreign investment for the development of its transport and communication complex on sufficiently favorable terms. As history would have it, virtually all domestic, interregional and other international routes running across the country coincide with each other, forming a favorable pattern of territorial transit arteries. That is why the establishment of international transportation corridors will help to develop the republic’s internal transportation system, so that investment in this infrastructure will not lead to an imbalance between the state’s internal and external interests. In this respect, it is particularly important today to formulate a correct strategy in relations with Russia, China, Kyrgyzstan and Uzbekistan.